The content of fatty acids in lipophilic extracts of Veronica chamaedrys L. and Veronica officinalis L. - Marchyshyn, S. M.; Milian, I. I. (Journal of Education, Health and Sport, 2016)
Marchyshyn S. M., Milian I. I. The content of fatty acids in lipophilic extracts of Veronica chamaedrys L. and Veronica officinalis L. Journal of Education, Health and Sport. 2016;6(3):91-96. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47673 http://ojs.ukw.edu.pl/index.php/johs/article/view/3427 https://pbn.nauka.gov.pl/works/720389 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. UDC 615.32+661.732.7]-092.4 THE CONTENT OF FATTY ACIDS IN LIPOPHILIC EXTRACTS OF VERONICA CHAMAEDRYS L. AND VERONICA OFFICINALIS L. S. M. Marchyshyn, I. I. Milian SHEI «I.Ya. Horbachevsky Ternopil State Medical University Ministry of Health of Ukraine» S.M. Marchyshyn, doctor of pharmacy, professor, I.I. Milian, master of pharmacy Summary There is indicated the results of the investigation of lipophilic fraction obtained from the herbs of Veronica chamaedrys L. and Veronica officinalis L., determined the yield of the lipophilic fraction in relation to the raw materials, settled the content of fatty acids in lipophilic extract. It is noted that linoleic and linolenic fatty acids dominated in the investigation materials. Keywords: fatty acids, herb, Veronica chamaedrys L., Veronica officinalis L., a gas chromatography-mass spectrometry.